Inflammatory Human Umbilical Cord-Derived Mesenchymal Stem Cells Promote Stem Cell-Like Characteristics of Cancer Cells in an IL-1β-Dependent Manner - Luo, Xiaohe (Biomed Res Int, 2018)
To ensure the safety of clinical applications of MSCs, thorough understanding of their impacts on tumor initiation and progression is essential. Here, to further explore the complex dialog between MSCs and tumor cells, umbilical cord-derived mesenchymal stem cells (UC-MSCs) were employed to be cocultured with either breast or ovarian cancer cells. Though having no obvious influence on proliferation or apoptosis, UC-MSCs exerted intense stem cell-like properties promoting effects on both cancer models. Cocultured cancer cells showed enriched side population, enhanced sphere formation ability, and upregulated pluripotency-associated stem cell markers. Human cytokine array and real-time PCR revealed a panel of MSC-derived prostemness cytokines CCL2, CXCL1, IL-8, and IL-6 which were induced upon coculturing. We further revealed IL-1β, a well-characterized proinflammatory cytokine, to be the inducer of these prostemness cytokines, which was generated from inflammatory UC-MSCs in an autocrine manner. Additionally, with introduction of IL-1RA (an IL-1 receptor antagonist) into the coculturing system, the stem cell-like characteristics promoting effects of inflammatory UC-MSCs were partially blocked. Taken together, these findings suggest that transduced inflammatory MSCs work as a major source of IL-1β in tumor microenvironment and initiate the formation of prostemness niche via regulating their secretome in an IL-1β-dependent manner.